Advances in the mechanism of high copper diets in restraining pigs growth. Issue 2 (16th December 2019) - Gao, Yang; Yang, Wenyan; Che, Dongsheng; Adams, Seidu; Yang, Lianyu
Abstract: High copper feed has been widely used as an inexpensive and highly effective feed additive to promote growth performance of pigs. However, long‐term feeding of high copper feed may reduce the growth‐promoting effects of copper, time‐dependent accumulation of copper in animal tissues and organs, and copper toxicity thereby reducing the growth performance of pigs. Due to the widespread effects of high copper supplementation in animals' diets, the benefits and drawbacks of high copper feeding in pigs have been reported in several studies. Meanwhile, few of these studies have systematically described the mechanism by which high copper diets restrain pig growth. Therefore, to address the concerns and give a better understanding of the mechanism of high copper diet in restraining pig growth in different systems, this paper reviews the research progress of long‐term supplementation of high copper on the growth of pigs and provides some suggestions and further research directions.